Migrating from Novell NetWare® to Windows NT™ Server 4. - Plumley, Sue (John Wiley & Sons, Inc., 1997)
"¿How will my files transfer? ¿How do i set up a print server? What kinds of adjustments will my users need to make? ¿Can i compress files in NT? ¿What is a domain? ¿Can i migrate more than one NetWare server at a time? If you're a NetWare network administrator who's considering migrating to Windows NT Server 4, you probably have hundreds of questions like these. In this step-by-step guide, bestselling author Sue Plumley answers all of your most pressing questions. Lear what to do, why you're doing it, and what order to do it in. Build skills and confidence for the inevitable customization work to come. Migrating from Novell NetWare to Windows NT Server 4 gives you technical coverage of Server set-up and administration. You'll get detailed checklists and network diagrams to prepare your system and your users for the new environment." (Copied from the back cover).